2016
DOI: 10.1682/jrrd.2014.12.0313
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of exposure to high-intensity blasts: Results on tests of central auditory processing

Abstract: Abstract-Patients who have recently experienced highintensity blasts are more likely to perform abnormally on tests developed to be sensitive to deficits of central auditory processing than were age-and hearing-matched individuals without blast exposures. Here, a group of 59 participants was recruited, 30 of whom were exposed to high-intensity blasts between 4 and 11 yr prior to testing and did not participate in the previous study, along with 29 controls similar in age and hearing thresholds to the blast grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 17 publications
4
32
0
11
Order By: Relevance
“…Among the chronic problems, studies have documented auditory dysfunction following both nonblast and blast-related mTBI. Despite the fact that few of these individuals have hearing outside the normal range on a clinical audiogram, a significant percentage report difficulty understanding speech in background noise as well as difficulty on other complex auditory tasks, such as understanding rapid speech or detecting small gaps in noise [5][6][7][8][9][10][11][12][13]. Difficulties with these tasks may result from damage to structures in the central auditory pathway which may be especially vulnerable to mTBI, including auditory brainstem nuclei, structures in the left temporal lobe, pathways between the thalamus and primary auditory cortex, the planum temporale, and the corpus callosum [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among the chronic problems, studies have documented auditory dysfunction following both nonblast and blast-related mTBI. Despite the fact that few of these individuals have hearing outside the normal range on a clinical audiogram, a significant percentage report difficulty understanding speech in background noise as well as difficulty on other complex auditory tasks, such as understanding rapid speech or detecting small gaps in noise [5][6][7][8][9][10][11][12][13]. Difficulties with these tasks may result from damage to structures in the central auditory pathway which may be especially vulnerable to mTBI, including auditory brainstem nuclei, structures in the left temporal lobe, pathways between the thalamus and primary auditory cortex, the planum temporale, and the corpus callosum [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although a medical chart review was also performed to determine if a clinical diagnosis of TBI had been made, blast-exposed participants without the clinical diagnosis of TBI were still included in the study, as previous work has indicated that patients who meet the DVBIC criteria for brain injury following blast exposure experience auditory dysfunction similarly to those who have received a blast-related diagnosis of TBI. 6,17,18,28 Additional exclusionary criteria included pure-tone hearing thresholds >30 dB hearing level (HL) at any test frequencies between 250 and 4000 Hz, threshold differences of >10 dB between the left and right ear at any test frequency, and diagnosis of mental health conditions associated with poor sensory gating including schizophrenia, bipolar disorder, obsessive compulsive disorder, and attention-deficit/hyperactivity disorder. Sixteen participants (all males) were admitted to the blast-exposed group (average age 36.9 years; age range 24–58 years), and 13 participants (2 females) were admitted to the control group (average age 38 years, age range 19–66 years).…”
Section: Methodsmentioning
confidence: 99%
“…9–11 The most common auditory complaints among these veterans include increased sensitivity to noise, poor speech understanding in the setting of competing background noise, difficulty understanding rapid speech, problems understanding speech on the telephone, difficulty following conversations among groups of people, poor recall of auditory information, and auditory fatigue. 5,6,9,12–16 Hearing problems often persist in spite of normal pure-tone hearing sensitivity, suggesting a central rather than peripheral locus of dysfunction. This assumption is corroborated by recent work showing that between 20% and 40% of veterans exposed to high-intensity blasts demonstrate abnormal performance on behavioral and electrophysiological assessments of the central auditory system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTBI group also scored higher on items that suggested problems with auditory attention and memory (i.e., difficulty memorizing information by listening and problems paying attention when people talk to me). Hoover et al (2017) found that 84% of their civilian cohort with mTBI reported speech-in-noise difficulty compared to 9% of their matched controls, and Gallun et al (2016) found 60% of their blast-exposed veteran participants scored as moderate-to-severe hearing handicap despite normal/near-normal hearing thresholds. Saunders et al (2015) also reported on veterans with blast exposure but included only those with normal or almost normal audiograms who specifically reported auditory difficulties (n = 99).…”
Section: Auditory and Postconcussion Symptom Reportingmentioning
confidence: 99%